2022
DOI: 10.3390/info13050254
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Inbound Travelers Experience and Satisfaction at Quarantine Hotels in Indonesia during the COVID-19 Pandemic

Abstract: The tourism and hospitality sectors contribute significantly to the Indonesian economy. Meanwhile, COVID-19 affects these sectors. During the pandemic, the Indonesian government applied quarantine regulations at designated hotels to support its tourism industry. Since COVID-19 is becoming endemic and travel bans are being relaxed, hotel satisfaction becomes a crucial factor in quarantine hotels. If guests have a positive experience while staying at these hotels, they are likely to return for a staycation or va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…In qualitative Study 1, we found that potential consumers believed that hotel booking during COVID-19 would be influenced by hotel factors and individual factors. Potential consumers would favor QHs since such hotels fulfilled more CSR, which is consistent with the finding in previous studies ( Handani et al, 2022 ; Sun et al, 2022 ), further confirming the idea that hotels fulfilling their social responsibility during the pandemic will be recognized by consumers. Based on the findings of the qualitative study, we conducted Study 2 to examine the differences in QH BI and NH BI of potential consumers as well as the internal mechanisms.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In qualitative Study 1, we found that potential consumers believed that hotel booking during COVID-19 would be influenced by hotel factors and individual factors. Potential consumers would favor QHs since such hotels fulfilled more CSR, which is consistent with the finding in previous studies ( Handani et al, 2022 ; Sun et al, 2022 ), further confirming the idea that hotels fulfilling their social responsibility during the pandemic will be recognized by consumers. Based on the findings of the qualitative study, we conducted Study 2 to examine the differences in QH BI and NH BI of potential consumers as well as the internal mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…In the face of the fear and uncertainty brought by COVID-19, consumers have become more concerned about the pandemic prevention and control measures hotels take to reduce health risks ( Sun et al, 2022 ). CSR initiatives can help hotels gain positive evaluation and recognition by consumers such as loyalty, public praise, and brand attachment ( Brown and Dacin, 1997 ; Sen and Bhattacharya, 2001 ; Lichtenstein et al, 2004 ; Marin et al, 2009 )Actively fulfilling social responsibility and improving sanitary conditions will contribute to CT, customer satisfaction and BI ( Rhou and Singal, 2020 ; Handani et al, 2022 ). When potential consumers perceive that QHs are actively fulfilling their social responsibility and believe that they can benefit from such CSR behaviors, they tend to act in a way that benefits the hotel, i.e., hotel BI.…”
Section: Study 2: Experimental Study On the Intention Of Potential Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…The data were collected using Outscraper which is an API tool to scrape data from the google maps [16]. Each review contains a set of information which includes hotel name, author's title, review text, and review rating (scale of [1][2][3][4][5].…”
Section: Methodsmentioning
confidence: 99%
“…As the policymakers, the government also can establish certain policies that support the recovery process of the tourism and hospitality industries. The Indonesian government has gradually made efforts to implement various policies to improve the ability to control and prevent Covid-19 and restore the tourism industry by implementing policies from largescale social restrictions (PSBB or PPKM), quarantine hotels for inbound travellers, and incentive regulations (Andariesta & Wasesa, 2022;Faeni et al, 2022;Handani et al, 2022), and CHSE as mentioned above.…”
Section: Introductionmentioning
confidence: 99%